Anticommunism in the West and its Encounter with the Theory of Totalitarianism in the Early Cold War - Papadimitriou, Despoina (The Historical Review/La Revue Historique, 2025)
The interweaving of anticommunist/totalitarian patterns of thought in Greece with those formulated in other Western countries invites a crossnational pursuit without a comparative evaluation. Anticommunism was linked to nationalism during the Greek Civil War, while antitotalitarianism created an ethical and political space for those opposed to totalitarianism and the communist regimes. It also formulated a semasiological field around notions such as freedom of speech, the captive mind, intellectual enslavement, anticommunist martyrs and the antithesis between truth and ideology/fanaticism.